Physical Activity Determinants of Female Teachers in Rasht County, Iran; Applying the Social Cognitive Theory - Rogheyeh Ashouri-ahmadgoorabi; Nooshin Rouhani-tonekaboni; Parisa Kasmaei; Maryam Shakiba; Tahereh Kamalikhah (Journal of Education and Community Health)
Aims: Inactivity among Iranian women is higher than in Iranian men. Since teachers are exposed to occupational damages, it is necessary to consider physical activity in teachers. The Social-Cognitive Theory (SCT) is a useful framework for understanding physical activity behavior. Therefore, the present research was aimed to determine physical activity determinants in female teachers based on SCT. Instrument & Methods: This analytic-cross sectional study was performed on 612 female schoolteachers of all educational levels of urban and rural areas of Rasht County using multi-stage random sampling in the 2019- 2020 academic years. The data collection instruments included demographic information, International Physical Activity Questionnaire– Short Form, and Social Cognitive Theory Questionnaire. In order to analyze the data, I used Independent Samples t-test, Analysis of Variance, Spearman Correlation Coefficient, and Multiple Linear Regression tests in SPSS 21 software. Findings: The age average of the teachers was 40.25±7.65. Of the total, 331 teachers (54.1%) had light physical activity (0-599 MET minutes/week). It observed the most direct correlation between self-efficacy (r=0.439) and exercise planning (r=0.513) with physical activity behavior. Constructs of exercise Planning (B=0.34, p=0.001) and Self-Efficacy (B=0.14, p=0.003) were the most significant predictors of physical activity and accounted for 17% and 12% of the variance, respectively. Conclusion: Constructs of exercise Planning and Self-Efficacy were the most important predictors of physical activity that can be used in designing interventions to promote physical activity in teachers.